2019
DOI: 10.1016/j.eneco.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between oil price shocks and stock returns revisited

Abstract: In this paper, we revisit the debate on the relationship between oil price shocks and stock market returns by replicating the quantile-on-quantile (QQ) regression model for the US stock market in Sim and Zhou (2015, Journal of Banking and Finance), and extending it to 15 countries. The classification of these countries as oil importers or oil exporters depends on their net position in crude oil trade. Our results indicate that the main finding by Sim and Zhou (2015) that large negative oil price shocks can bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 30 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…Cook and Fosten (2018) look at two "rockets and feathers" papers, confirming the findings by Bachmeier and Griffin (2003) but showing that the results of Liu et al (2010) are sensitive to specification. Filip et al (2017) confirm the weak and varying relationship between food and fuel prices, found by Zhang et al (2010), for a much wider range of indicators. Mastroeni et al (2018) revisit a number of papers on the chaotic behaviour of energy prices, confirming some earlier results but not others.…”
supporting
confidence: 68%
“…Cook and Fosten (2018) look at two "rockets and feathers" papers, confirming the findings by Bachmeier and Griffin (2003) but showing that the results of Liu et al (2010) are sensitive to specification. Filip et al (2017) confirm the weak and varying relationship between food and fuel prices, found by Zhang et al (2010), for a much wider range of indicators. Mastroeni et al (2018) revisit a number of papers on the chaotic behaviour of energy prices, confirming some earlier results but not others.…”
supporting
confidence: 68%
“…In the context of oil prices, increase in oil prices could result in increased costs, and consequently affecting corporate profitability/shareholder value, and thus negatively affecting stock prices (Filis, Degiannakis, & Floros, 2011). The assumptions of asset pricing theory suggest that elements that have possible systematic impact on investment opportunities or consumption behaviour (e.g., oil prices), are likely to affect the pricing of large stock aggregates (Tchatoka, Masson, & Parry, 2018, p. 15). Wan (2005) presents interesting theoretical justification about the asymmetric impact of oil prices on stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of oil price shocks on different aspects of an economy have been widely discussed in the literature (see e.g. Park and Ratti, 2008;Jimenez-Rodriguez, 2008;Farzanegan and Markwardt, 2009;Iwayemi and Fowowe, 2011;Aydın and Acar, 2011;Scholtens and Yurtsever, 2012;Cunado and de Gracia, 2014;Gao et al, 2014;Kang et al, 2014;Zhang and Qu, 2015;Tsai, 2015;Cunado et al, 2015;Ju et al, 2016;Zhang and Tu, 2016;Nusair, 2016;Zhao, 2016;Kim et al, 2017;Cross and Nguyen, 2017;Lee et al, 2017;Karnizova and Reza, 2018;Moshiri and Moghaddam, 2018;Nasir et al, 2018;Ioannidis and Ka, 2018;Oladosu et al, 2018;Lorusso and Pieroni, 2018;Tchatoka et al, 2018;Herrera et al, 2019;Lee and Lee, 2019;Nusair and Olson, 2019;Grigoli, et al, 2019;Bergmann, 2019). However, the mentioned studies are different from our paper because what they consider as oil price shocks is not a same concept as what we refer to as the 1973 oil price shock.…”
Section: Introductionmentioning
confidence: 65%